Seni Membaca dan Memahami Bacaan: Strategi Literasi dalam Pembelajaran IPS Terpadu di SD IT Alfityah - Syarif, Ahmad; Aramudin (Journal of Practice Learning and Educational Development, 2026)
The Merdeka Curriculum emphasizes the importance of literacy as a basic competency for the 21st century, in which students are not only required to be able to read texts, but also to be able to read social and cultural contexts. This study aims to describe the application of literacy strategies through the art of reading and understanding various types of reading materials in Integrated Social Studies (IPS) learning at Alfityah Islamic Elementary School. The background of this study is the low ability of students to understand IPS reading texts that are conceptual and contextual in nature. The research used a qualitative descriptive method with a field study approach through observation, interviews, and documentation. The results showed that the literacy strategies applied, such as active reading, layered reading, and reflective discussion, were able to improve students' understanding of social concepts, critical thinking skills, and interest in reading. Reading activities are not only directed at recognizing textual information, but also at understanding the social and moral meanings of the reading content. This study confirms that the art of reading in Integrated Social Studies is key to building critical literacy and social character in elementary school students.